Battery positive electrode binder applied to power battery, preparation method of battery positive electrode binder, battery positive electrode plate and power battery

Through the combination of acrylic monomer, aqueous nanosilica and sodium alginate, the problem of insufficient performance of the positive electrode adhesive of the power battery is solved, and a positive electrode adhesive with high adhesion and high mechanical properties is achieved, suitable for power Battery and avoid environmental pollution from oily adhesives.

CN119220210AInactive Publication Date: 2024-12-31GUANGZHOU FUSIDA CHEM PROD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411640521.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The mechanical properties and adhesiveness of the existing power battery positive electrode adhesive are insufficient, and the oily adhesive is highly polluted to the environment. The mixing degree of polyacrylic acid and carbon nanotubes in the water-based adhesive is insufficient, which affects the performance.

Method used

Using a combination of acrylic monomer, aqueous nanosilica and sodium alginate, the aqueous nanosilica is uniformly dispersed through hydrogen bonding and stirring to form a battery positive electrode adhesive with high bonding force and high mechanical properties. Preparation by adding constant temperature polymerization method.

Benefits of technology

The high bonding force and high mechanical properties of the battery positive electrode adhesive are achieved, suitable for large-scale production, and environmental pollution of oily adhesives is avoided due to the use of aqueous nanosilica and sodium alginate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138307220000061
    Figure BDA0005138307220000061
  • Figure BDA0005138307220000071
    Figure BDA0005138307220000071
Patent Text Reader

Abstract

The invention relates to a battery positive electrode binder applied to a power battery, a preparation method of the battery positive electrode binder, a battery positive electrode plate and the power battery. The battery positive electrode binder comprises 80-100 parts of an acrylic monomer, 3-7 parts of water-based nano silicon dioxide, 5-10 parts of sodium alginate, 200-300 parts of water and 0.1-0.5 part of an initiator. The water-based nano silicon dioxide, the sodium alginate and the polyacrylic acid can be mutually entangled or covalently bonded. The water-based nano silicon dioxide can improve the mechanical property and binding power of the positive electrode binder, and the sodium alginate can improve the mechanical property of the positive electrode binder. And the acrylic acid-water-based nano silicon dioxide-sodium alginate system is very high in mechanical property and binding power because the components are uniformly distributed and form covalent bonds or are mutually entangled. Solubilization of acrylic acid can be realized by sodium alginate, and the acrylic acid and the water-based nano silicon dioxide are positioned in a molecular chain of the sodium alginate under the action of hydrogen bonds, so that a positive electrode adhesive with a certain particle size can be formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to a battery positive electrode binder applied to a power battery and a preparation method thereof, a battery positive electrode sheet and a power battery. Background Art

[0002] The positive electrode binder of the power battery needs to have high mechanical properties and high adhesion, and the positive electrode binders with the above characteristics in the prior art are mostly oily binders. However, oily binders will pollute the environment.

[0003] The Chinese patent application with publication number CN111952593A published on November 17, 2020 discloses an aqueous binder for positive electrode sheets of lithium-ion power batteries and a preparation method thereof. The aqueous binder includes 60 to 70 parts by weight of water, a reaction amount of LiOH, 30 to 40 parts by weight of polyacrylic acid, and 0.1 to 0.6 parts by weight of functionalized carbon nanotubes, wherein the pH of the aqueous binder is 5.0 to 6.5, and the solid content of the polyacrylic acid is 50 to 65%, and the functionalized carbon nanotubes include a carbon nanotube core and a hydroxylated carbon layer attached to the carbon nanotube core. However, due to the problem of insufficient mixing of polyacrylic acid and carbon nanotubes, its mechanical properties and adhesion are affected. Summary of the invention

[0004] In order to solve the problems existing in the above-mentioned prior art, the first object of the present invention is to provide a battery positive electrode binder applied to a power battery, wherein the battery positive electrode binder has the advantages of excellent mechanical properties and bonding properties.

[0005] In order to solve the problems existing in the above-mentioned prior art, a second object of the present invention is to provide a method for preparing a battery positive electrode binder used in a power battery.

[0006] In order to solve the problems existing in the above-mentioned prior art, the third object of the present invention is to provide a positive electrode plate of a battery.

[0007] In order to solve the problems existing in the above-mentioned prior art, the third object of the present invention is to provide a power battery.

[0008] In order to achieve the first object of the present invention, the following technical scheme is adopted:

[0009] The present invention provides a battery positive electrode binder for power batteries, which comprises the following components in parts by weight: 80-100 parts of acrylic acid monomer, 3-7 parts of water-based nano silicon dioxide, 5-10 parts of sodium alginate, 200-300 parts of water, and 0.1-0.5 parts of initiator.

[0010] During the specific implementation, the hydroxyl and carboxyl groups of sodium alginate form hydrogen bonds with the hydroxyl groups on the surface of water-based nano-silicon dioxide, which causes the water-based nano-silicon dioxide to be evenly dispersed in water under the dispersion of sodium alginate, avoiding the agglomeration of water-based nano-silicon dioxide, which results in its inability to fully copolymerize with acrylic acid. Acrylic acid is added dropwise to the mixture of sodium alginate-water-based nano-silicon dioxide-water, and then copolymerized. At this time, acrylic acid is close to water-based nano-silicon dioxide due to hydrogen bonding and stirring, and reacts with the hydroxyl groups on the surface of water-based nano-silicon dioxide and sodium alginate, polymerizing on the surface of water-based nano-silicon dioxide and sodium alginate to form polyacrylic acid chains and entangle with each other, so that the prepared positive electrode binder has high bonding force and high mechanical properties. Water-based nano-silicon dioxide can improve the mechanical properties and bonding force of the positive electrode binder, sodium alginate can improve the mechanical properties of the positive electrode binder, and acrylic acid polymerization makes the positive electrode binder have basic properties. In addition, the acrylic acid-aqueous nano-silica-sodium alginate system has very high mechanical properties and bonding strength because the components are evenly distributed and form covalent bonds or entanglements with each other. Sodium alginate can solubilize acrylic acid, and hydrogen bonding allows acrylic acid and aqueous nano-silica to be coexisting in the sodium alginate molecular chain, thereby forming the positive electrode binder particles of a certain particle size.

[0011] It should be noted that water-based nano-silica is hydrophilic, in contrast to oily nano-silica, which is hydrophobic.

[0012] Preferably, the particle size of the aqueous nano-silica is 10-100 nm.

[0013] Preferably, the aqueous nano-silica is in a water-dispersed colloid or solid state.

[0014] In a specific implementation, the water-based nano-silica is in a water-dispersible colloidal state or a solid state. Compared with solid water-based silica, the water-dispersible colloidal water-based nano-silica can be dispersed in water more easily and effectively and is less likely to agglomerate.

[0015] Preferably, the purity of sodium alginate is 99% or above.

[0016] The present invention also provides a method for preparing a positive electrode binder for a power battery as described in any of the above technical solutions, comprising the following steps: dissolving sodium alginate in water, adding aqueous nano-silicon dioxide after a period of reaction while stirring, and after sufficient reaction, adding acrylic acid monomer and initiator simultaneously by dropwise addition, and polymerizing under stirring and constant temperature to obtain the positive electrode binder.

[0017] In the specific implementation, sodium alginate is dissolved in water and then aqueous nano-silica is added, so that the aqueous nano-silica can be dispersed by sodium alginate and effectively dispersed in water, and then the acrylic acid monomer and the initiator are added by dropwise addition, firstly the -COOH in the acrylic acid monomer is attracted and reacted with the -OH in the aqueous nano-silica and the sodium alginate through hydrogen bonds, and then based on this, polyacrylic acid segments are generated on the aqueous nano-silica and the sodium alginate. In order to fully react, polymerization is required under stirring and constant temperature to obtain the positive electrode binder. Before the acrylic acid monomer and the initiator are added dropwise, the temperature needs to be adjusted to 75°C-85°C and the stirring speed needs to be adjusted to 3000-4000rpm before the subsequent steps can be carried out. During the reaction, an acid is used as a catalyst and the pH is maintained at 4-6.

[0018] Preferably, the temperature for heating sodium alginate is 50° C.-55° C., the stirring speed is 500-1000 rpm, and the reaction time is 2-2.5 hours.

[0019] Preferably, the reaction temperature for adding aqueous nano-silica is 50° C.-55° C., the stirring speed is 3500-4000 rpm, and the reaction time is 1-1.5 hours.

[0020] Preferably, the dropping rate of the acrylic acid monomer is 0.2-0.5 mL / min, and the dropping rate of the initiator is 0.1-0.15 mL / min per 200-300 mL of water.

[0021] Preferably, the reaction temperature during the dropwise addition of acrylic acid monomer and initiator is 75° C.-85° C., the stirring speed is 3000-4000 rpm, the initiator is ammonium persulfate, the initiator concentration is 1-2 g / L, and the reaction time is 6-12 hours.

[0022] In specific implementation, before dropping the acrylic acid monomer and the initiator, the temperature needs to be adjusted to 75°C-85°C and the stirring speed needs to be adjusted to 3000-4000rpm before the subsequent steps can be carried out. Before dropping the acrylic acid monomer, the inhibitor needs to be removed.

[0023] Preferably, a terminator is also included, and the terminator is sulfuric acid, which is added directly in an amount of 1-5 parts.

[0024] In specific implementation, the polymerization reaction can be terminated naturally due to exhaustion of reactants, or by adding a terminator.

[0025] The present invention also provides a battery positive electrode plate, which is made using any of the above-mentioned battery positive electrode binders applied to power batteries.

[0026] The present invention also provides a power battery, which includes the above-mentioned battery positive electrode plate.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The battery positive electrode binder used in power batteries of the present invention has the advantage that the hydroxyl and carboxyl groups of sodium alginate form hydrogen bonds with the hydroxyl groups on the surface of water-based nano-silica, which results in the water-based nano-silica being evenly dispersed in water under the dispersion of sodium alginate, avoiding the agglomeration of water-based nano-silica, thereby enabling the water-based nano-silica to fully copolymerize with the acrylic acid monomer. Acrylic acid is added dropwise to the mixture of sodium alginate-water-based nano-silica-water, and then copolymerized. At this time, acrylic acid approaches water-based nano-silica due to hydrogen bonding and stirring, and reacts with the hydroxyl groups on the surfaces of water-based nano-silica and sodium alginate, polymerizes on the surfaces of water-based nano-silica and sodium alginate to form polyacrylic acid chains and entangle with each other, so that the prepared battery positive electrode binder has high bonding force and high mechanical properties. Water-based nano-silica can improve the mechanical properties and bonding force of the battery positive electrode binder, sodium alginate can improve the mechanical properties of the battery positive electrode binder, and acrylic acid polymerizes to give the battery positive electrode binder basic properties. In addition, the acrylic acid-aqueous nano-silica-sodium alginate system has very high mechanical properties and bonding strength because the components are evenly distributed and form covalent bonds or entanglements with each other. Sodium alginate can solubilize acrylic acid, and hydrogen bonding allows acrylic acid and aqueous nano-silica to be coexisting in the sodium alginate molecular chain, forming battery positive electrode adhesive particles of a certain particle size. Therefore, the battery positive electrode binder used in power batteries has the advantages of excellent mechanical properties and bonding properties.

[0029] (2) The method for preparing a positive electrode binder for a power battery of the present invention is simple and applicable to large-scale production.

[0030] (3) The positive electrode sheet of a battery of the present invention has the advantages of good peeling strength and tensile strength.

[0031] (4) A power battery of the present invention has all the advantages of the above-mentioned positive electrode sheet. DETAILED DESCRIPTION

[0032] The present invention discloses a battery positive electrode binder for use in a power battery. The technical solution of the present invention will be further described below using specific embodiments and comparative examples. Unless otherwise specified, the main components of the products in the embodiments, method examples, application examples and comparative examples of the present invention are all purchased from commercially available products.

[0033] Water-based nano-silica, 40 nm, HL-200 type, 99.8%, was purchased from Hubei Huifu Nanomaterials Co., Ltd.

[0034] Sodium alginate, high purity, CAS No. 9005-38-3, was purchased from Shanghai Darui Fine Chemicals Co., Ltd.

[0035] Example 1

[0036] A battery positive electrode binder used in a power battery comprises the following components by weight: 80 parts of acrylic acid monomer, 3 parts of water-based nano-silicon dioxide, 5 parts of sodium alginate, 300 parts of water, and 0.1 parts of an initiator.

[0037] Sodium alginate was dissolved in water, heated at 50°C, stirred at 500rpm, and aqueous nano-silica was added after reacting for 2 hours while stirring. The reaction temperature was 50°C and the stirring was performed at 3500rpm. After reacting for 1 hour, acrylic acid monomer and initiator were added simultaneously by dropwise addition, wherein the dropping rate of acrylic acid monomer was 0.2mL / min and the dropping rate of initiator was 0.1mL / min for every 300mL of water, and polymerization was performed under stirring and constant temperature. The reaction temperature when dropping acrylic acid monomer and initiator was 75°C, the stirring speed was 3000rpm, the initiator was ammonium persulfate, the initiator concentration was 1g / L, the reaction time was 6 hours, and 1 part of sulfuric acid was added 15 minutes before the end of the reaction to obtain a battery positive electrode binder for power batteries.

[0038] Example 2

[0039] A battery positive electrode binder used in power batteries comprises the following components in parts by weight: 100 parts of acrylic acid monomer, 7 parts of water-based nano-silicon dioxide, 10 parts of sodium alginate, 300 parts of water, and 0.3 parts of initiator.

[0040] Sodium alginate was dissolved in water, heated at 55°C, stirred at 1000rpm, and aqueous nano-silica was added after reacting for 2.5 hours while stirring. The reaction temperature was 55°C and the mixture was stirred at 4000rpm. After reacting for 1.5 hours, acrylic acid monomer and initiator were added simultaneously by dropwise addition, wherein the dropping rate of acrylic acid monomer was 0.5mL / min and the dropping rate of initiator was 0.15mL / min for every 200mL of water, and polymerization was carried out under stirring and constant temperature. The reaction temperature when acrylic acid monomer and initiator were added dropwise was 85°C, the stirring speed was 4000rpm, the initiator was ammonium persulfate, the initiator concentration was 2g / L, the reaction time was 12 hours, and 5 parts of sulfuric acid were added 10 minutes before the end of the reaction to obtain a battery positive electrode binder for power batteries.

[0041] Example 3

[0042] A battery positive electrode binder used in a power battery comprises the following components in parts by weight: 90 parts of acrylic acid monomer, 5 parts of water-based nano-silicon dioxide, 7 parts of sodium alginate, 250 parts of water, and 0.5 parts of an initiator.

[0043] Sodium alginate was dissolved in water, heated at 52°C, stirred at 700rpm, and aqueous nano-silica was added after reacting for 2.3 hours while stirring. The reaction temperature was 52°C and the stirring was performed at 3600rpm. After reacting for 1.2 hours, acrylic acid monomer and initiator were added simultaneously by dropwise addition, wherein the dropping rate of acrylic acid monomer was 0.3mL / min and the dropping rate of initiator was 0.12mL / min for every 25mL of water, and polymerization was performed under stirring and constant temperature. The reaction temperature when dropping acrylic acid monomer and initiator was 80°C, the stirring speed was 3600rpm, the initiator was ammonium persulfate, the initiator concentration was 1.5g / L, the reaction time was 10 hours, and 3 parts of sulfuric acid were added 12 minutes before the end of the reaction to obtain a battery positive electrode binder for power batteries.

[0044] Example 4

[0045] A battery positive electrode plate is prepared using the battery positive electrode binder for power batteries obtained in any one of Examples 1 to 3.

[0046] Example 5

[0047] A power battery is made from a battery positive electrode sheet of Example 4.

[0048] Comparative Example 1

[0049] A battery positive electrode binder, the difference between this comparative example and Example 1 is that sodium alginate is not added. The remaining components and preparation method are the same as those in Example 1.

[0050] Comparative Example 2

[0051] A battery positive electrode binder, the difference between this comparative example and Example 1 is that no water-based nano silicon dioxide is added. The remaining components and preparation method are the same as those in Example 1.

[0052] Comparative Example 3

[0053] A battery positive electrode binder, the difference between this comparative example and Example 1 is that no acrylic acid monomer is added. The remaining components and preparation method are the same as those in Example 1.

[0054] Method example

[0055] Weigh 50 parts of lithium cobalt oxide and 10 parts of acetylene black, and carry out ball milling reaction at a ball milling speed of 4000 rpm for 30 minutes. Then add the powder after the ball milling reaction to the battery positive electrode binder prepared by the present invention, stir at 2000 rpm and react at 55°C. After reacting for 1 hour, filter out the solid matter, coat it on aluminum foil, completely dry it in an oven at 65°C, and roll it to a thickness of 100 μm to prepare a sample.

[0056] Application Examples 1 to 3 adopt the method of Method Example and use the battery positive electrode binders prepared in Examples 1 to 3 respectively. Application Examples 4 to 6 adopt the method of Method Example and use the positive electrode binders prepared in Comparative Examples 1 to 3 respectively.

[0057] Experimental test:

[0058] The test standards and methods adopted include GB / T 2792-2014 and substrate stretching method.

[0059] The substrate stretching method is as follows:

[0060] The positive electrode binders in the above-mentioned embodiments 1-3 and comparative examples 1-3 were respectively evenly applied to the first aluminum sheet, 1cm×2cm surface, and the coating thickness was controlled to be 1mm. The second aluminum sheet, 1cm×2cm, was covered on the binder surface. The first aluminum sheet and the second aluminum sheet were stretched along 180° to test their tensile strength. The average value was taken after 5 parallel tests.

[0061] In addition, the peel strength of the samples of Application Examples 1 to 6 was measured.

[0062] The specific results are shown in Table 1

[0063] Table 1 Test results of embodiments, comparative examples and application examples

[0064]

[0065]

[0066] The test results of Examples 1 to 3 and Application Examples 1 to 3 show that the battery positive electrode binder for power batteries prepared by the present invention has the effects of high mechanical properties and high bonding strength. Compared with Example 1, Application Example 1 and Application Example 4, the peel strength and tensile strength performance of Comparative Example 1 are both reduced. This is because the reference document 1 does not add sodium alginate, which will cause the water-based nano-silica to agglomerate in water, thereby affecting the polymerization reaction of acrylic acid and water-based nano-silica. Compared with Example 2, Application Example 2 and Application Example 5, the tensile strength performance of Comparative Example 2 is reduced. This is because the absence of water-based nano-silica will cause sodium alginate and polyacrylic acid to be unable to react covalently and entangle with water-based nano-silica as the core, and the water-based nano-silica itself does not contribute to the mechanical properties and bonding strength of the positive electrode binder, thereby reducing the mechanical properties and bonding strength of the positive electrode binder. Compared with the performance of Example 3 and Comparative Example 3 and their application examples, the performance of Comparative Example 3 is reduced because the positive electrode binder cannot obtain the basic performance produced by the polymerization of acrylic acid monomers without the use of acrylic acid monomer polymerization. Therefore, the battery positive electrode binder used in power batteries prepared by the present invention has excellent mechanical properties and bonding properties.

[0067] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, horizontal" and "top, bottom" are usually for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the scope of protection of the present invention.

[0068] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. A battery positive electrode binder used in a power battery, characterized in that: The invention comprises the following components in parts by weight: 80-100 parts of acrylic acid monomer, 3-7 parts of water-based nano-silicon dioxide, 5-10 parts of sodium alginate, 200-300 parts of water and 0.1-0.5 parts of initiator.

2. The positive electrode binder for power batteries according to claim 1, characterized in that: The particle size of the aqueous nano-silica is 10-100 nm.

3. The positive electrode binder for power batteries according to claim 1 or 2, characterized in that: The aqueous nano-silica is in a water-dispersible colloid or solid state; and / or The purity of sodium alginate is above 99%.

4. A method for preparing a positive electrode binder for a power battery according to any one of claims 1 to 3, characterized in that: The steps include: The formulated amount of sodium alginate is dissolved in water, and then aqueous nano-silicon dioxide is added while stirring. After the reaction, acrylic acid and an initiator are added dropwise, and a polymerization reaction is carried out under stirring and constant temperature to obtain the battery positive electrode binder for power batteries.

5. The method for preparing a positive electrode binder for a power battery according to claim 4, characterized in that: The temperature for dissolving sodium alginate in water is 50°C-55°C, the stirring speed is 500-1000rpm, and the reaction time is 2-2.5 hours.

6. The method for preparing a positive electrode binder for a power battery according to claim 4, characterized in that: The reaction temperature for adding aqueous nano-silica is 50°C-55°C, the stirring speed is 3500-4000rpm, and the reaction time is 1-1.5 hours.

7. The method for preparing a positive electrode binder for a power battery according to claim 4, characterized in that: The dropping method is: in every 200-300 mL of water, the dropping rate of acrylic acid monomer is 0.2-0.5 mL / min, and the dropping rate of initiator is 0.1-0.15 mL / min; and / or The reaction temperature when the acrylic acid monomer and the initiator are added dropwise is 75° C.-85° C., the stirring speed is 3000-4000 rpm, the initiator is ammonium persulfate, the initiator concentration is 1-2 g / L, and the reaction time is 6-12 hours.

8. The method for preparing a positive electrode binder for a power battery according to claim 7, characterized in that: During the polymerization reaction, a terminator is also added, wherein the terminator is sulfuric acid, which is added directly in an amount of 1-5 parts.

9. A positive electrode plate of a battery, characterized in that: The invention is prepared by using the battery positive electrode binder for power batteries as described in any one of claims 1 to 8.

10. A power battery, characterized in that: Made from the battery positive electrode sheet described in claim 9.

Citation Information

Patent Citations

  • Flame-retardant binding material for power battery module as well as preparation process and application of flame-retardant binding material

    CN116063960A

  • Slurry composition for lithium ion secondary battery negative electrode, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2016048633A

  • Composition for preventing, ameliorating or treating coronavirus infectious disease comprising herbal medicine mixture extract as effective component

    KR102532944B1

  • Alginate-containing compositions for use in battery applications

    US20120088155A1